Private Criminological Theory in the Form of Criminology of Political Crime (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The paper analyses the existing Russian and foreign criminological approaches to deﬁning the phenomenon of state crimes. The author highlights the advantages and drawbacks of different approaches to this criminological category and offers an instrumental deﬁnition of political crimes.